The Cult of the Mother of God in Byzantium: Texts and Images. Edited by Leslie Brubaker and Mary B. Cunningham - Panagopoulos, Spyros P. (The journal of theological studies, 2013)
In recent years several studies have been published regarding the Mother of God (‘Theotokos’ in Greek) and her cult in Byzantium. This volume aims to collect all the questions arising from the study of different sources, including archaeological, homiletic, apocryphal, liturgical, and artistic. These essays focus on the origin and the development of the Marian cult from the fourth to the twelfth centuries. Some questions which are put under discussion are the following: although we know that the cult of the Holy Virgin was established officially after iconoclasm, there is a range of numerous pre-iconoclast monuments, portraits, and religious objects.